Design and analysis of a double-acting nonlinear wideband piezoelectric energy harvester under plucking and collision. (15th January 2022) - He, Lipeng; Liu, Lei; Zhou, Jianwen; Yu, Gang; Sun, Baoyu; Cheng, Guangming
Abstract: This paper proposes a double-acting nonlinear wideband piezoelectric energy harvester under plucking and collision(W-PEH) for energy during rotation. The device is mainly composed of a base, rectangular piezoelectric patches, circular piezoelectric generating units and permanent magnets. The circular power generation units are constructed by using the nonlinear magnetic coupling mechanism and the contact frequency conversion principle. The nonlinearity caused by the magnetic force makes the circular piezoelectric power generation units work stably and efficiently at low speeds. And the contact-type collision excitation enables the circular piezoelectric patches inside the circular piezoelectric generating units to produce greater deformation and output a higher voltage. The rectangular piezoelectric patches are excited by the plucking, and the vibration amplitude is greater at high speeds, and it also produces a higher output voltage. Two different excitations make W-PEH's working frequency band wider, and the overall output voltage is also higher. The electromechanical coupling dynamics model of the system was constructed from Hamilton's principle and the magnetic dipole theory. The experimental results indicate that W-PEH can work effectively in different frequency bands. Under the load of 10 KΩ, the peak-to-peak power of the 150r/min integrated device is 0.350W, and that of the 450r/min integrated device is 0.107W. Highlights: Combines a nonlinear magnetic coupling with contact frequency conversion principle. It works well under both low and high speeds excitation. Two excitations make W-PEH's working frequency band wider, and the power is higher. It can supply power for micro-electronic devices.